2014
DOI: 10.1111/ajps.12091
|View full text |Cite
|
Sign up to set email alerts
|

Partisans in Robes: Party Cues and Public Acceptance of Supreme Court Decisions

Abstract: The public perceives the Supreme Court to be a legal institution. This perception enables the Court's legitimacy-conferring function, which serves to increase public acceptance of its decisions. Yet, the public acknowledges a political aspect to the Court as well. To evaluate how the public responds to the different images of the Supreme Court, we investigate whether and how depictions of specifically partisan (e.g., Republican) Court rulings shape public acceptance of its decisions while varying institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 42 publications
5
84
3
Order By: Relevance
“…Cross-national research indicates that legitimacy is not always sufficient to produce acquiescence, especially in relatively young courts (e.g., Gibson and Caldeira 2003), but research in the United States has generally supported the hypothesis that legitimacy can induce acquiescence (see Spence 2003a, 2005). The decisions of legitimate institutions, even when handing down unpopular decisions, seem to carry with them an obligation to accept and obey (Levi, Sacks, and Tyler 2009;Tyler 1990Tyler , 2006; but see Nicholson and Hansford 2014).…”
Section: Positivity Theory and Acquiescence To Objectionable Court Rumentioning
confidence: 99%
“…Cross-national research indicates that legitimacy is not always sufficient to produce acquiescence, especially in relatively young courts (e.g., Gibson and Caldeira 2003), but research in the United States has generally supported the hypothesis that legitimacy can induce acquiescence (see Spence 2003a, 2005). The decisions of legitimate institutions, even when handing down unpopular decisions, seem to carry with them an obligation to accept and obey (Levi, Sacks, and Tyler 2009;Tyler 1990Tyler , 2006; but see Nicholson and Hansford 2014).…”
Section: Positivity Theory and Acquiescence To Objectionable Court Rumentioning
confidence: 99%
“…Such heuristic cue‐following allows people to make quick assessments on complex matters in order to help make sense of the world around them in an efficient and largely effective manner (e.g., Kahneman ; Nicholson and Hansford ; Salamone ). In experimental settings, researchers have found that the public is responsive to partisan source cues about the Court (Clark and Kastellec ; Nicholson and Hansford ) and that the ideology of the opinion author in particular serves as a source cue that conditions individual agreement with court decisions—even those that run counter to an individual's expressed policy preferences (Boddery and Yates ). In the section that follows, we build on these insights to lay out an account that describes how the attribution of a U.S. Supreme Court decision on a case affects the public's feelings about that decision.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On the other hand, Nicholson and Hansford () cast doubt on this view, as they find minimal evidence that attributing a decision as coming from the U.S. Supreme Court changes how heavily the public relies on partisan cues in its evaluations of a decision. While attributing the outcome of a case to the Court increased public acceptance of the decision in certain instances, the effect was quite small.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Initiated largely by Bartels and Johnston ( 2013 ), and joined more recently by Christenson and Glick ( in press ) (and, to a lesser and somewhat different degree, Nicholson & Hansford, 2014 ), this view posits a far stronger relationship between specifi c and diffuse supports than heretofore imagined. 8 For example, Bartels and Johnston claim to have discovered a strong effect of disappointment in a decision of the Court, with those learning that the Court had ruled against their position on the issue of whether the government can monitor the internet expressing less institutional support than those who were told the Court had ruled in favor of the respondents' position.…”
Section: The Specifi C Support -Diffuse Support Linkagementioning
confidence: 99%
“…It should not be surprising, therefore, that these symbols infl uence how people perceive and evaluate courts. As Nicholson and Hansford ( 2014 ) observe: "Since the Court dresses itself in legal symbols, both literally (i.e., the wearing of black robes by the justices) and fi guratively (by emphasizing reliance on the Constitution, precedent, and legal norms), its image is decidedly positive relative to the elected branches of government" (p. 2). suggest that judicial symbols can play an important role in conditioning the relationship between the two forms of support.…”
Section: The Role Of Symbols In Mitigating the Impact Of Policy Disapmentioning
confidence: 99%